The procedure of the UN Security Council - Bailey, Sydney D. (Sydney Dawson), 1916-1995.; Daws, Sam. (Oxford : Clarendon, 1998)
This edition encompasses the many changes in Council procedure that have occurred since the end of the Cold War, while retaining pertinent historical material. It includes details of UN peace-keeping and forecasts of the Council's work programme.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United Nations. -- Security Council